2019
DOI: 10.1002/cyto.b.21840
|View full text |Cite
|
Sign up to set email alerts
|

The Quantification of Minimal Residual Disease Pre‐ and Post‐Unmanipulated Haploidentical Allograft by Multiparameter Flow Cytometry in Pediatric Acute Lymphoblastic Leukemia

Abstract: BackgroundThis study aimed to determine the impact of the pre‐ and post‐minimal residual disease (MRD) status as well as the peri‐transplant MRD kinetics on clinical outcomes in pediatric ALL patients who received haploidentical allografts.MethodsA retrospective study (n = 166) was performed. MRD was determined using multiparameter flow cytometry.ResultsPediatric ALL patients with pre‐MRDneg had a lower cumulative incidences of relapse (CIR) compared to those with pre‐MRDpos (19.7% vs. 41.2%, P = 0.009). Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
4
19
1
Order By: Relevance
“…Consistent with previous studies, [ 14 , 16 20 , 23 , 25 , 64 ] our study showed that patients with post-MRD + suffered higher CIR and poorer survival than post-MRD − patients. In addition, we also found that post-MRD + at different time points was related to a higher incidence of relapse and a lower probability of LFS and OS, which was consistent with the results of Bader et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous studies, [ 14 , 16 20 , 23 , 25 , 64 ] our study showed that patients with post-MRD + suffered higher CIR and poorer survival than post-MRD − patients. In addition, we also found that post-MRD + at different time points was related to a higher incidence of relapse and a lower probability of LFS and OS, which was consistent with the results of Bader et al .…”
Section: Discussionsupporting
confidence: 93%
“…A previous study [ 18 ] also showed that the positive MRD at the time points, including days +30, +60, +90, +180, and +365 after allo-SCT, were inversely correlated with event-free survival and positively correlated with CIR in pediatric ALL. More recently, we reported the association of both quantitative and qualitative pre-transplantation MRD (pre-MRD) [ 11 ] as well as post-transplantation MRD (post-MRD) [ 25 ] with increased CIR and inferior survival in patients with ALL who underwent haploidentical allograft transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…The pooled results evidenced a higher relapse risk (hazard ratio 3.26; p < 0.05) and lower RFS (hazard ratio 2.53; p < 0.05) in patients with positive pre-transplant MRD in comparison to those with negative MRD. Further studies published 2018–2020 in different transplant settings (related and unrelated donor or haploidentical HCT) and mixed age populations with large percentages of AYA, confirmed the unfavorable prognostic role of pre-HCT MRD pos , with a relapse incidence of 32–73% vs. 19.7–24% in pre-HCT MRD neg subsets [ 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. Thus, achieving an MRD neg status before HCT in MRD pos patients should improve the overall transplantation outcome.…”
Section: Mrd In Aya Ph− Allmentioning
confidence: 79%
“…transplantation outcomes in patients with T-ALL. In addition, we also tried to establish a risk score principally based on the dynamic peri-HSCT MRD combined with other parameters, such as remission status pre-HSCT and onset of chronic GVHD demonstrated by others [12,26,27] and us [2,16,19] , which might provide better relapse risk determination for T-ALL patients.…”
mentioning
confidence: 99%